Industry 4.0 and New Paradigms in the Field of Metal Forming - Milutinović, Mladomir (Array, 2021)
Over the last few year, the metalworking sector has been undergoing rapid and radical transformations driven by global competition and the revision of the production focus that is being moved from mass customization to mass individualization. A results of this is introduction of new manufacturing strategies such as Industry 4.0, a concept that combines cyber-physical systems and promote communication and connectivity. Therefore, this concept changes not only the face of the manufacturing systems but also causes transformation of existing business models and the society as a whole. This paper deals with the recent trends and paradigms in the field of metal forming, resulting from the concept of Industry 4.0 and the modern market challenges. The maim attention is paid on the flexibility of manufacturing systems and recent developments in design of smart forming tools.